Unions, Wages and Total Compensation in Canada: An Empirical Study - Renaud, Stéphane (Relations industrielles / Industrial Relations, 1998)
This study presents the first empirical evidence of the impact of unions on benefits and total compensation in Canada. It also provides new evidence on the union wage impact and union wage differentials for a wide range of selected groups in the labor market. Using micro data from the Canadian General Social Survey of 1989, the results show that the union impact is to increase total compensation by 12.4%, compared to an impact of 10.4% on wages. Even though the union impact on total compensation is 2% greater than the impact on wages, given that benefits comprise only about 6% of total compensation in this sample, the percentage impact of unions on benefits is estimated to be 45.5%. This latter estimate implies a very substantial impact on unions on benefits in Canada, as large or larger than those reported in the US.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Compensation plans; Employee benefits; Impact analysis; Labor Unions; Memberships; Regression analysis; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Wages & salaries